The Formation of the Solid/Liquid Electrolyte Interphase (SLEI) on NASICON‐Type Glass Ceramics and LiPON. Issue 19 (18th August 2020) - Busche, Martin R.; Weiss, Manuel; Leichtweiss, Thomas; Fiedler, Carsten; Drossel, Thomas; Geiss, Matthias; Kronenberger, Achim; Weber, Dominik A.; Janek, Jürgen
Abstract: Most electrochemical energy storages (battery cells) consist of solid electrodes separated by a liquid electrolyte. If electrode materials are—at least partially—soluble in the electrolyte, detrimental mass transport between both electrodes (electrode cross‐talk) occurs. The shuttle mechanism in lithium–sulfur batteries and leaching of Mn in high voltage cathode materials are important examples. Implementing a solid electrolyte (SE) membrane between the electrodes is a comprehensible approach to suppress undesired mass transport but additional resistances arise due to charge transport across the SE and charge transfer through the solid/liquid electrolyte interfaces. The latter contribution is often overlooked as its determination is challenging; however, these interface properties are crucial for practical application. In previous work, a resistive solid/liquid electrolyte interphase "SLEI" has been found at the interface between the SE lithium aluminum germanium phosphate in contact with a liquid ether‐based electrolyte. Here, the aim is deeper insight into this interphase formation, referring to a lithium‐ion conducting glass ceramic (NASICON‐type) and the commonly used thin‐film ion conductor lithium phosphorous oxide nitride. The growth of the SLEI is monitored by a combination of electrochemical characterization, X‐ray photoelectron spectroscopy, and time‐of‐flight secondary ion mass spectrometry. Abstract : Solid electrolyte membranes can be used in liquid‐electrolyte‐based batteries to prevent detrimental chemical cross‐talk. At the newly created interface between liquid (LE) and solid electrolytes (SE), a highly resistive solid/liquid electrolyte interphase (SLEI) may form. Here, this phenomenon is reported for different solid and liquid electrolytes, the formation is monitored, and differences in the composition based on the applied materials are elucidated.